The incidence, characteristics, and outcomes of stroke and seizure in critically ill surgical patients: A multicenter cohort study of thai surgical intensive care units (THAI-SICU study) - Siraklow S. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: To explore the incidence, characteristics, and outcomes of patients affected with new onset of stroke and seizure in the surgical intensive care unit (SICU). Material and Method: This study identified new onset of stroke and seizure in 4,652 patients admitted to our multicenter prospective cohort study, a collaboration of nine university-affiliated surgical ICUs in Thailand between April 2011 to January 2013. Results: The authors found new stroke and seizure events at 0.2% and 1%, respectively. The significant characteristics found in stroke and seizure patients included: reason for ICU admission, American Society of Anesthesiologists (ASA) physical status classification, and severity of patients at ICU admission (evaluated by APACHE-II and SOFA day score in first 24 hours of ICU admission). In terms of outcomes, there was higher ICU mortality in both stroke and seizure groups than in nonstroke and non-seizure groups (18% vs. 36% vs. 9%, p < 0.001, respectively). In addition, ICU length of stay among stroke and seizure patients was also longer than non-stroke and non-seizure groups (6 (4-18) vs. 10 (4-16) vs. 2 (1-4) days, p < 0.001, respectively). However, multivariable regression analysis showed a statistical significance only in longer duration of ICU stay in stroke (6.07 days; 95% CI: 3.34-8.80) and seizure (3.88 days; 95% CI: 2.15-5.62) when compared with nonstroke and non-seizure patients, adjusted by ASA, APACHE-II and SOFA score). Conclusion: From Thai-SICUs study, patients admitted to surgical ICU who developed new episodes of stroke and seizure had longer ICU length of stay when adjusted by their severity score.